Dbo/Henji Modulates Synaptic dPAK to Gate Glutamate Receptor Abundance and Postsynaptic Response. - Manyu Wang; Pei-Yi Chen; Chien-Hsiang Wang; Tzu-Ting Lai; Pei-I Tsai; Ying-Ju Cheng; Hsiu-Hua Kao; Cheng-Ting Chien (PLoS Genetics)
In response to environmental and physiological changes, the synapse manifests plasticity while simultaneously maintains homeostasis. Here, we analyzed mutant synapses of henji, also known as dbo, at the Drosophila neuromuscular junction (NMJ). In henji mutants, NMJ growth is defective with appearance of satellite boutons. Transmission electron microscopy analysis indicates that the synaptic membrane region is expanded. The postsynaptic density (PSD) houses glutamate receptors GluRIIA and GluRIIB, which have distinct transmission properties. In henji mutants, GluRIIA abundance is upregulated but that of GluRIIB is not. Electrophysiological results also support a GluR compositional shift towards a higher IIA/IIB ratio at henji NMJs. Strikingly, dPAK, a positive regulator for GluRIIA synaptic localization, accumulates at the henji PSD. Reducing the dpak gene dosage suppresses satellite boutons and GluRIIA accumulation at henji NMJs. In addition, dPAK associated with Henji through the Kelch repeats which is the domain essential for Henji localization and function at postsynapses. We propose that Henji acts at postsynapses to restrict both presynaptic bouton growth and postsynaptic GluRIIA abundance by modulating dPAK.